Post-glacial dispersal patterns of Northern pike inferred from an 8800 year old pike (Esox cf. lucius) skull from interior Alaska - Wooller, MJ; Gaglioti, B; Fulton, TL; Lopez, A; Shapiro, B (eScholarship, University of California, 2015)
© 2015 Elsevier Ltd. The biogeography of freshwater fish species during and after late-Pleistocene glaciations relate to how these species are genetically organized today, and the management of these often disjunct populations. Debate exists concerning the biogeography and routes of dispersal for Northern pike (Esox lucius) after the last glaciation. A hypothesis to account for the relatively low modern genetic diversity for E. lucius is post-glacial radiation from refugia, including lakes from within the un-glaciated portions of eastern Beringia. We report the remains of a Northern pike (E. cf. lucius) skull, including bones, teeth, bone collagen and ancient DNA. The remains were preserved at a depth of between 440 and 446cm in a 670cm long core of sediment from Quartz Lake, which initiated at ~11,200calyr BP in interior Alaska. A calibrated accelerator mass spectrometer (AMS) radiocarbon age of the collagen extracted from the preserved bones indicated that the organism was dated to 8820calyr BP and is bracketed by AMS values from analyses of terrestrial plant macrofossils, avoiding any potential aquatic reservoir effect that could have influenced the radiocarbon age of the bones. Scanning electron microscope images of the specimen show the hinged tooth anatomy typically of E.lucius. Molar C:N (3.5, 1σ=0.1) value of the collagen from the specimen indicated well-preserved collagen and its mean stable nitrogen isotope value is consistent with the known predatory feeding ecology of E.lucius. Ancient DNA in the bones showed that the specimen was identical to modern E.lucius. Our record of E.lucius from interior Alaska is consistent with a biogeographic scenario involving rapid dispersal of this species from glacial refugia in the northern hemisphere after the last glaciation.